2017
DOI: 10.1002/2016gl071240
|View full text |Cite
|
Sign up to set email alerts
|

UV photochemistry of carboxylic acids at the air‐sea boundary: A relevant source of glyoxal and other oxygenated VOC in the marine atmosphere

Abstract: Photochemistry plays an important role in marine dissolved organic carbon (DOC) degradation, but the mechanisms that convert DOC into volatile organic compounds (VOCs) remain poorly understood. We irradiated carboxylic acids (C7–C9) on a simulated ocean surface with UV light (<320 nm) in a photochemical flow reactor and transferred the VOC products into a dark ozone reactor. Glyoxal was detected as a secondary product from heptanoic, octanoic, and nonanoic acid (NA) films, but not from octanol. Primary glyoxal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 67 publications
7
60
0
Order By: Relevance
“…[2][3][4][5]40 In agreement, the same VOC classes were observed for the biofilm samples investigated in this work (Table 1 and Supplementary Information). In particular, not only saturated 15 oxygenated VOCs, such as aldehydes and ketones, but also unsaturated and functionalized VOCs were observed (e.g., alkenes, dienes, unsaturated aldehydes or ketones).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…[2][3][4][5]40 In agreement, the same VOC classes were observed for the biofilm samples investigated in this work (Table 1 and Supplementary Information). In particular, not only saturated 15 oxygenated VOCs, such as aldehydes and ketones, but also unsaturated and functionalized VOCs were observed (e.g., alkenes, dienes, unsaturated aldehydes or ketones).…”
Section: Resultssupporting
confidence: 74%
“…3,42 It has been demonstrated that photosensitizers, e.g., humic acids, can initiate photochemical VOC production in the presence of surfactants by transition to a triplet state after UV/visabsorption. 2,3,5,10,40 Subsequently, such excited molecules can trigger radical chemistry through H-30 abstraction from other organics, such as fatty acids, followed by addition of molecular oxygen. 43,44 Furthermore, photosensitizers were shown to be enriched in SMLs on aqueous solutions, 5,45,46 thus,…”
Section: Resultsmentioning
confidence: 99%
“…Although SML chemical composition is complex and not fully understood, it contains both saturated and unsaturated fatty acids (32,34,35). Gas-phase production of smaller and more oxygenated molecules from these model SML constituents can occur via three different mechanisms: direct photooxidation (17,26), photosensitized oxidation (27,28,31), or heterogeneous oxidation (29). Thus, OVOCs can be produced from the SML in the presence of light with or without the action of photosensitizers, or in the presence of gas-phase oxidants such as ozone or the hydroxyl radical.…”
Section: Significancementioning
confidence: 99%
“…Recent laboratory studies (17,(26)(27)(28)(29)(30)(31) have uncovered novel mechanisms for the emission of OVOCs to the MBL involving chemistry at the interface between the ocean and atmosphere, where the sea surface microlayer (SML) can be enriched in organic matter. The thickness of the SML is typically about 50 μm (32), and substantial SML enrichments (relative to underlying bulk seawater) in surfactants, saccharides, and plankton exudates have been observed globally in both eutrophic and oligotrophic waters (e.g., ref.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation